Association of baseline plasma des‐acyl ghrelin level with the response to rikkunshito in patients with functional dyspepsia. Issue 2 (28th January 2016) - Togawa, Koji; Matsuzaki, Juntaro; Kobayakawa, Masao; Fukushima, Yasushi; Suzaki, Fumio; Kasugai, Kunio; Nishizawa, Toshihiro; Naito, Yuji; Hayakawa, Toshihiko; Kamiya, Takeshi; Andoh, Takashi; Yoshida, Hideo; et al.
Abstract: Background and Aim: We recently conducted a randomized placebo‐controlled trial on the efficacy and safety of rikkunshito, a standardized Japanese herbal medicine, for the treatment of functional dyspepsia (FD). The present post‐hoc study aimed to evaluate the differences in clinical characteristics between responders and non‐responders among FD patients who received rikkunshito for 8 weeks. Methods: Rikkunshito responders were defined by using a global patient assessment. Candidate predictors included age, gender, smoking, alcohol consumption, body mass index, comorbidity, Helicobacter pylori infection, plasma levels of acyl ghrelin and des‐acyl ghrelin, severity of dyspeptic symptoms, FD subgroup, previous medication, and the type of recruiting institution (clinic or hospital). We calculated hazard ratios (HRs) by using Cox regression analysis with the factors that were indicated to be associated with responders. Results: We assigned 83 and 42 patients to responder and non‐responder categories, respectively. Lack of alcohol consumption (HR, 2.04; 95% confidence interval, 1.08–3.88) and low plasma des‐acyl ghrelin levels (< 177 fmol/mL; HR, 2.42; 95% confidence interval, 1.24–4.73) were significantly associated with the efficacy of rikkunshito. Lack of alcohol consumption was associated with the efficacy of rikkunshito especially among H .  pylori ‐infected participants. On the other hand, the low plasma des‐acyl ghrelin was associated with the efficacy of rikkunshito especially among H .  pylori ‐negative participants. Conclusions: A low baseline level of plasma des‐acyl ghrelin was associated with an increased treatment efficacy of rikkunshito against FD. Lack of alcohol consumption was also clinically useful for predicting the response to rikkunshito.